BANGUNAN CAMPURAN DENGAN RUANG HIJAU SEBAGAI ASPEK DOMINAN PERANCANGAN - Novalentina Novalentina; Doddy Yuono (Jurusan Arsitektur dan Perencanaan, 2021)
Dwelling (also a residence, a residence) is a self-contained accommodation unit used by one or more households as a home; such as a house, apartment, mobile home, household, vehicle, other